RESEARCH BRAVE SPACES AND ZINE-MAKING: DISRUPTIVE TOOLS FOR EXPLORING DIGITAL SEXUAL INTIMACIES - Reschiglian, Rachele; Scarcelli, Cosimo Marco (AoIR Selected Papers of Internet Research, 2026)
The study of digital sexual intimacies presents ethical and methodological challenges, often framed by anxieties around sex, public life, and the internet (Tiidenberg, 2018, 2020). Traditional qualitative methods tend to be extractive and risk-centered. Instead, creative, participatory, and multimodal approaches foster inclusive, reflexive, and non-hierarchical research environments (Knowles & Cole, 2007; Mannay, 2016). Art-based methods, particularly zine-making, have been used across disciplines to engage marginalized groups (McNicol, 2019; Etengoff, 2015). As self-published, DIY pamphlets, zines offer a non-linear, multimodal space for expression and collective knowledge production (Duncombe, 1997; Lovata, 2007). They challenge traditional data collection by integrating text, visuals, and intertextual elements, making them particularly valuable in queer and subcultural research contexts (Downes et al., 2013). This study introduces the Research Brave Space (RBS) concept, shifting from ‘safe spaces’ to settings where participants courageously engage with sensitive topics (Arao & Clemens, 2013). Implemented through zine-making workshops with queer young adults in Italy, RBS prioritizes care, adaptability, and agency. These workshops facilitated cognitive, emotional, and physical accessibility, fostering collective engagement and self-representation. Participants reported increased agency and deeper reflexivity, illustrating the method’s transformative potential. Zine-making as RBS disrupts academic methodologies, advocating for ethics of care and participatory research in digital sexual intimacies. Embracing discomfort and creative non-linearity fosters more inclusive knowledge production, challenging scholars to rethink engagement with vulnerable subjectivities in social sciences.